PENGARUH RASIO KEUANGAN TERHADAP PERTUMBUHAN LABA (Studi Kasus Pada Perusahaan Property Dan Real Estate Yang Terdaftar Di BEI Tahun 2016-2020) - Anggraeni, Nava Yansi (Jurnal Manajemen & Bisnis Jayakarta, 2022)
This study aims to determine the effect of financial ratios on profit growth in property and real estate companies listed on the Indonesia Stock Exchange for the 2016-2020 period. The dependent variable in this study is profit growth, while the independent variable is financial ratios consisting of Current Ratio, Debt to Equity Ratio, Total Asset Turnover and Net Profit Margin. The population in this study are all property and real estate sector companies. The samples obtained were 17 companies using purposive sampling method. This study uses secondary data obtained from financial reports on the Indonesia Stock Exchange. In performing data analysis techniques using multiple linear regression. By using the F test, the results of the study indicate that there is a significance of the independent variable on the dependent variable. Through the t test, the variables of Total Asset Turnover and Net Profit Margin partially have a significant effect on profit growth. While the Current ratio and Debt to Equity Ratio partially have no effect on profit growth.